2017
DOI: 10.1083/jcb.201701104
|View full text |Cite
|
Sign up to set email alerts
|

Actin turnover maintains actin filament homeostasis during cytokinetic ring contraction

Abstract: Many cytokinetic actomyosin ring components undergo dynamic turnover, but its function is unclear. Chew et al. show that continuous actin polymerization ensures crucial F-actin homeostasis during ring contraction, without which ring proteins organize into noncontractile clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 43 publications
(69 reference statements)
5
56
0
1
Order By: Relevance
“…A similar trend was observed when Jas-stabilized wild-type, myo2-S1, and cdc3-124 myo2-S1 ghosts were incubated with ATP even at the lower temperature of 24°C ( Figure 4C). This is similar to our previous observations with cell ghosts of the well characterized temperature-sensitive myo2-E1 allele, rings from which fail to contract upon ATP addition, even at the permissive temperature of 24°C (Mishra, Kashiwazaki et al 2013, Palani, Chew et al 2017). In addition, we found that Jasstabilized actomyosin rings in cell ghosts prepared from cdc3-124 myo2-S2 (which suppresses cdc3-124, but less well compared to myo2-S1) also underwent very slow ATP-dependent contraction at 34°C ( Figure S2B and C) and at 24°C ( Figure S2D).…”
Section: S1 Cellssupporting
confidence: 92%
See 1 more Smart Citation
“…A similar trend was observed when Jas-stabilized wild-type, myo2-S1, and cdc3-124 myo2-S1 ghosts were incubated with ATP even at the lower temperature of 24°C ( Figure 4C). This is similar to our previous observations with cell ghosts of the well characterized temperature-sensitive myo2-E1 allele, rings from which fail to contract upon ATP addition, even at the permissive temperature of 24°C (Mishra, Kashiwazaki et al 2013, Palani, Chew et al 2017). In addition, we found that Jasstabilized actomyosin rings in cell ghosts prepared from cdc3-124 myo2-S2 (which suppresses cdc3-124, but less well compared to myo2-S1) also underwent very slow ATP-dependent contraction at 34°C ( Figure S2B and C) and at 24°C ( Figure S2D).…”
Section: S1 Cellssupporting
confidence: 92%
“…Previous work has shown that single actin filaments and networks of actin filaments are broken and disassembled by myosin II through buckling (Murrell andGardel 2012, Vogel, Petrasek et al 2013). Previous work in S. japonicus has shown that isolated cytokinetic rings break into a series of clusters in a myosin II dependent manner, which is reversed and normal contraction upon ATP addition ensues, when the isolated cytokinetic rings are pre-incubated with Jasplakinolide (Chew, Huang et al 2017). Our work may provide in vivo evidence for a role for myosin II in actin filament disassembly and turnover, also consistent with the work in cytokinetic mammalian cells (Murthy and Wadsworth 2005).…”
Section: Myo2-s1 Suppresses Direct Pharmacological Perturbation Of Thsupporting
confidence: 88%
“…Rapid filament turnover may be important for local network homeostasis -i.e. to maintain uniform filament density and prevent local tearing and/or clumping of contractile ring components (Chew et al, 2017). At the same time, filament turnover provides an effective way to dissipate local resistance to the rapid remodeling of actin networks that underlies flow and filament realignment (McFadden et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Actin turnover during ring contraction is important for actin filament homeostasis and proper contraction, as shown in cytokinesis models including NRK cells and Schizosaccharomyces japonicus (S. japonicus ; Guha et al, ; Chew et al, ) as well as in wound healing models such as Drosophila embryos (Kobb et al, ). Mathematical modeling of the node model of S. pombe cytokinetic ring contraction also suggests that protein turnover is required to stabilize the ring, as myosin aggregation could decrease contractile tension and cause the ring to fracture (Thiyagarajan et al, ).…”
Section: Maintaining a Dynamically Stable Cr During Assembly And Contmentioning
confidence: 99%
“…In Dictyostelium cytokinesis, which does not involve a standard CR, actin crosslinkers dynacortin and fimbrin interact with myosin II to create differentials in stiffness and contractility between the equator and the poles that modulate the shape of the cell (Zhang and Robinson, 2005;Reichl et al, 2008;Descovich et al, 2018) Actin turnover. Actin turnover during ring contraction is important for actin filament homeostasis and proper contraction, as shown in cytokinesis models including NRK cells and Schizosaccharomyces japonicus (S. japonicus; Guha et al, 2005;Chew et al, 2017) as well as in wound healing models such as Drosophila embryos (Kobb et al, 2017). Mathematical modeling of the node model of S. pombe cytokinetic ring contraction also suggests that protein turnover is required to stabilize the ring, as myosin aggregation could decrease contractile tension and cause the ring to fracture (Thiyagarajan et al, 2017).…”
Section: Actin Dynamicsmentioning
confidence: 99%